Exploring Gender Differences in Achieving Worklife Balance: A Study of Hospitality Employees in the Republic of Serbia - Snežana Knežević; Dragan Vukolić; Lóránt Dénes Dávid; Tamara Gajić (Journal of Agronomy, Technology and Engineering Management, 2025)
In recent years, the hospitality industry has faced increasing challenges in retaining qualified staff, with work-life balance emerging as a critical factor in employee satisfaction and retention. Despite extensive research on work-life balance in various sectors, limited attention has been paid to the specific dynamics within the hospitality sector in developing economies. The objective of this research is to examine the impact of job and family demands, as well as work-family conflict, on work-life balance among employees in the hospitality sector in the Republic of Serbia, including an analysis of the moderating role of gender. Using Structural equation modeling, significant negative effects of these demands and conflicts on work-life balance were identified, with impacts being more pronounced among women. The innovative aspect of the research lies in the integration of moderating effects and analysis specific to the hospitality sector, providing insight into key employee challenges. The findings contribute to advancing academic discourse and provide guidelines for creating strategies that can improve human resource sustainability in the hospitality sector and employee work-life balance.